SULL'ETÀ TERZIARIA DEI CALCARI Dl UBAGA, SUCCESSIONE Dl BORGHETTO D'ARROSCIA-ALASSIO (ALPI MARITTIME) (Rivista italiana di Paleontologia e Stratigrafia, 2020)
The Borghetto d' Arroscia sequence is constituted by three turbiditic formations; the age of the different units is difficult to determine both because of scarsness of paleontological data and of their uncertain interpretation. Particularly the presence of lower cenozoic foraminifera in the Ubaga Limestones is debated. The discovery, in the studied section, of paleocenic—lower eocenic Morozovella allows now to state the Iower cenozoic age of the whole calcareous formation.